THE INFLUENCE OF DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE - Zulaspan Tupti; Muhammad Arif (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
Performance plays an important role for improving progress or change in a better direction to achieve the company's goals thus in essence performance is a result of work achieved by a person or group in an organization in accordance with the authority with their respective responsibilities in order to achieve organizational goals. The purpose of this study: to know the influence of discipline on performance at PT PLN (Persero) To know the influence of motivation on the performance of employees at PT PLN (Persero) to know the influence of discipline and motivation on the performance of employees at PT PLN (Persero). There is an influence of discipline and motivation on the performance of employees at PT. PLN (Persero) UIP. Sumatran power plant. There is a motivational influence on employee performance on the influence of discipline and motivation on employee performance at PT. PLN (Persero) UIP. Sumatran power plant. There is a disciplinary influence on the performance of employees at PT PLN (Persero) In this study in the use of associative approaches.approach and quantitative Discipline and motivation have a significant effect on employee performance means that the more improved discipline then kinerj will increase and if the motivation is given better then the performance will also improve significantly.